Transplantation: Polyomavirus Nephropathy and the Risk of Specific Immunosuppression Regimens - Christine Wu; Parmjeet Randhawa; Jerry McCauley (The Scientific World Journal)
BK virus is ubiquitously present in the latent state in humans, and awareness of the importance of BK polyomavirus is emerging among the kidney transplant community. First discovered in 1971 in the urine of a renal transplant recipient, BK virus nephropathy (BKVN) has come to be recognized as a significant cause of genitourinary disease and potential graft loss in the kidney transplant patient. In this review, we discuss the risk factors, available methods of diagnosis and therapeutic monitoring, and current approaches to therapy of BKVN.